CERM-3726 - J. Castañer; R.T. Owen (Drugs of the Future, 1982)
Objective In mammals, a lower testicular temperature is required for normal spermatogenesis. Testicular temperature can increase due to multiple factors, including lifestyle-related exposures, ultimately leading to damage to germ cells and impaired sperm parameters. Nigella sativa (black seed) has been reported to improve sperm parameters and exhibits a wide range of therapeutic properties. This study investigated the effects of black seed on antioxidant and anti-inflammatory activity in testicular tissue of adult male mice following scrotal hyperthermia. Methods Twenty-four male mice were randomly assigned to control, hyperthermia, and hyperthermia+black seed (Hyper+BS) groups. In the hyperthermia group, the animals' testes were exposed to water at 43 °C for 20 minutes, five times on alternate days. In the treatment group, following induction of hyperthermia, animals received black seed (300 mg/kg/day) orally for 35 days. At the end of the experiment, animals were euthanized for histological and molecular analyses. Results Black seed treatment conferred significant protective effects. Total sperm count and motility were significantly improved in the Hyper+BS group compared with the hyperthermia group (p≤0.0001 and p=0.0266, respectively). Black seed administration also significantly reduced tumor necrosis factor-α and interleukin-1β levels (p=0.0012 and p=0.0003, respectively). In addition, B-cell lymphoma 2 (Bcl-2) gene expression and glutathione levels were significantly increased in the Hyper+BS group (p=0.0038 and p≤0.0001, respectively). Conclusion These findings suggest that black seed may serve as a low-risk supportive natural supplement for preserving male fertility under conditions of scrotal hyperthermia. However, its routine clinical application requires validation through well-designed human studies.